Modelling of collapse settlement by effective stress and shear strength interaction for granite residual soil / Ismacahyadi Bagus Mohamed Jais - Mohamed Jais, Ismacahyadi Bagus (Institute of Graduate Studies, UiTM, 2014)
Over the years, consolidation settlement has always been associated with effective stress increase. However, in unsaturated soils, volume change behaviour of soils due to wetting is always complex due to changes of the soil when it is inundated. The main objectives of this research are to evaluate the simulation of foundations on unsaturated soil using various soil models incorporating loading and wetting collapse of the soil and to verify the settlement behaviour through physical model and laboratory shear strength test on unsaturated soil samples. The double wall triaxial apparatus was used to determine the unsaturated shear strength of the soil following Curved Surface Envelope Soil Shear Strength Model.